Konten בְּרִית dengan Abraham yang Misional dan Implikasinya Bagi Misi Yang Holistik - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2024)
This study examines the Abrahamic covenant in the Book of Genesis, with a focus on its missional dimension. The covenant בְּרִית (berith) with Abraham concerns not only the blessings for Abraham's descendants but also the calling to bring restoration to all of humanity and God's creation. Through a qualitative method and content analysis of biblical texts and related literature, this research explores the implications of the Abrahamic covenant within the context of God's global mission, which encompasses spiritual, social, economic, and ecological restoration. This study affirms that Jesus Christ, as the Messiah, fulfils the covenant, expanding the church's mission, which is not limited to spiritual aspects but also includes social and ecological transformation. The findings of this study offer a new understanding of the application of the Abrahamic covenant in the church's mission and the restoration of a more just and sustainable world.